Goodbye, Dragon Inn - Cai, Mingliang 1957-; Liao, Pen-Jung 1949-; Lee, Kang-Sheng 1968-; Chen, Hsiang-Chyi; Mitamura, Kiyonobu (Second Run, 2020)
"In Taipei City, a cavernous old picture palace is about to close its doors forever. A meagre audience, the remaining few staff, and perhaps even a ghost or two, watch King Hu's wuxia classic Dragon Inn - each haunted by memories and desires evoked by cinema itself. An exquisite, wryly funny and tender tribute to the experience of movie-going, Tsai Ming-Liang's poignant love letter to cinema is one of the most beguiling and beloved dramas of modern times and is now widely regarded as a classic. Presented here in a new 4K restoration, Goodbye, Dragon Inn is more ravishing and hypnotic than ever." [secondrundvd]
Original: Taiwan 2003
Special features: presented from the director-approved HD transfer of the new 4K restoration of the film ; an exclusive, newly filmed interview with director Tsai Ming-Liang ; Madam Butterfly (2009): world premiere on home video of Tsai Ming-Liang's remarkable short film interpretation of the classic story ; 20-page booklet featuring a new essay by curator and critic Tony Rayns, plus a personal appreciation by filmmaker Apichatpong Weerasethakul ; world premiere on Blu-ray
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc